Factors influencing the understanding of diabetic retinopathy complications among individuals with type 2 diabetes mellitus: A qualitative study - Rif'atunnailah Mat Isa; Chong Mei-Chan; Lee Wan Ling; Tajunisah Iqbal; Mohd Iman Saiful Suhardi; Thandar Soe@Sumaiyah Jamaludin (Faculty of Nursing Universitas Padjadjaran, 2025)
Background: The incidence of diabetes mellitus continues to rise steadily over the years, contributing to a significant increase in the risk of developing eye-related complications. The escalating burden of vision-related complications urge the early prevention measures for type 2 diabetes mellitus population. Purpose: Explore factors influencing the understanding of diabetic retinopathy among participants with type 2 diabetes mellitus who attended a diabetic clinic in a tertiary teaching hospital in Malaysia. Methods: This study employed a descriptive qualitative design using purposive sampling. From March to April 2021, three focus group discussions ranging in length from 30 minutes to an hour were performed utilising a semi-structured interview guide conducted with nine participants (five women and four men) aged 35 to 65 visited the diabetic clinic. Participants included in the study were who had type 2 diabetes mellitus diagnosed after six months or more. Data retrieved was thematically analysed using ATLAS/ti software, following the qualitative data analysis stages. Results:. Two themes emerged: challenges in practicing self-care and facilitating factors for health education. Subthemes within the challenges of practicing self-care included lack of knowledge about eye anatomy, changes in vision quality, concerns about medication intake, issues with glucose monitoring, challenges in nutritional management, and alternative practices. Subtheme for facilitating factors for health education included team work for giving health education, elements in diabetic retinopathy health education and teaching aid. Conclusions: Despite the availability of health education materials in the clinical context, participants identified a need for greater depth in diabetic retinopathy implications. Future studies and efforts include developing educational programs.